A fair green economy? Studies of agriculture, energy and waste initiatives in Malaysia - Adnan Hezri; Rospidah Ghazali (United Nations Research Institute for Social Development (UNRISD), 2011)
This paper proposes that a green economy needs also to be a fair economy. Following broader global trends, in 2009 the Malaysian government established the basic architecture for green economy by incorporating a green technology portfolio into the newly established Ministry of Energy, Green Technology and Water. This was followed by a suite of interventionist policy instruments. However, Malaysia's approach raises the question whether the full range of social, economic and environmental goals is considered in its policy objectives, since a strictly economic approach to sustainability risks marginalizing the social equity aspects of green economy. Parallel to the debate on sustainability, the social dimension of green economy has proven elusive both in definitional and substantive terms. There is no single understanding of integrated/comprehensive greening coming from either green growth, green economy or global green new deal discourses. However, the allocation of green goods and services is considered key, and it is recognized that this will eventually demand greater resources (not just economic) to achieve the necessary level of greening. For these reasons, although green economy does present an alternative pathway for development, it only partially resurrects the broader vision of sustainability as originally outlined by the sustainable development concept. For instance, focusing on green growth does not automatically lead a community to pathways to sustainability. Likewise, pro-poor investment alone cannot guarantee the diffusion of green projects that can lead to positive socioeconomic development outcomes. Since established poverty reduction programmes do not necessarily target the environment and vice versa, a green economy must integrate both poverty and environmental objectives. Malaysia's national green economy framework reflects a mainstream economics framing, such as that of the United Nations Environment Programme (UNEP) and the Organisation for Economic Co-operation and Development (OECD)...
Keywords: 330